Islamic And Western Ethical Perspectives On Mandatory Vaccination Policy For Children In Malaysia - Abdullah, Fathin Najiha Binti; Yusof, Danial Bin (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This study explores into the discussion of vaccination mandate for children in Malaysia from Islamic and Western ethical perspectives using the descriptive qualitative method of content analysis from journal articles and books as well as thematic analysis from the interviews with the Malaysian parents. Based on the study, the concept of Maslahah Mursalah and Maqasid Syariah were used from Islamic ethics and theory of Duty-based ethics (Deontology) and Utiliniarism (Ontology) were used from Western ethics to analyse the issue. The opinions of the parents of the Malaysian were studied as well and majority shows positive response towards the idea vaccination mandate for the children in Malaysia. The relation between these two distinct perspectives were explored to understand further before coming into conclusion that both of them shows relatively positive idea about vaccination mandate for children can be implemented in Malaysia with increase awareness and knowledge should be given to all parents prior punishing them for refusal.